Anemia with and without iron deficiency during pregnancy and association with adverse birth outcomes: BRINDA Project - Liu, Lei; Luo, Hanqi; Werner, Rochelle E.; Jefferds, Maria Elena D.; Addo, Yaw; Suchdev, Parminder S.; Usha, Ramakrishnan; Nguyen, Phuong Hong; Dewey, Kathryn G.; Ramírez-Luzuriaga, Maria J.; Young, Melissa F.; Ko, Yi-An (2025)
Objectives: To investigate association between anemia status along with the changes during pregnancy and birth outcomes (including preterm birth, small-for-gestational age [SGA], and low birth weight [LBW]). Methods: Data from the Biomarkers Reflecting Inflammation and Nutritional Determinants of Anemia (BRINDA) Project included 7 datasets (RCT) across 6 countries (n=7,176). Pregnant women were categorized as having IDA (anemia per WHO cutoffs and iron deficiency [inflammation-adjusted serum ferritin < 15 μg/L or soluble transferrin receptor >8.3 mg/L]), non-IDA, or no anemia based on the first study visit. In addition, for women with two or more visits (n=6163), biomarkers from the first and last visits were used to define any change in anemia status (e.g., from IDA to non-IDA), resulting in 9 combinations of anemia status change. Associations between first-visit anemia status and the changes during pregnancy with adverse birth outcomes were assessed using modified Poisson regression to obtain relative risk estimate (RR). Models adjusted for age, inflammation, dataset, socioeconomic status, study intervention, and malaria. Results: At the first visit (median 13 weeks gestation), 6.4% had IDA and 15.2% had non-IDA. IDA vs. no anemia was associated with a higher risk of preterm birth (RR=1.55, p< 0.01), while non-IDA was not associated with any adverse birth outcomes. Compared with women without anemia throughout pregnancy, having no-anemia (first visit) to IDA (last visit) was associated with a reduced risk of SGA (RR=0.86, p=0.03) and LBW (0.73, p< 0.01), but having no anemia to non-IDA was associated with an increased risk of SGA (1.12, p=0.04) and LBW (1.27, p< 0.01). Having non-IDA to no anemia had a lower risk of SGA (0.77, p=0.04) vs. those stayed with non-IDA. Conclusions: IDA early in pregnancy is associated with an increased risk of preterm birth. Changes in anemia status across pregnancy show mixed effects on birth outcomes and better understanding the underlying mechanisms may be useful to reduce adverse outcomes.